Deck the Halls: A Course to Build the Master Floral Designer Program Through the Pandemic and Beyond - James M. DelPrince; Patricia R. Knight (Journal of Human Sciences and Extension)
MSU Extension developed a virtual workshop on holiday floral design using cut ornamental evergreens in 2020 during the COVID-19 pandemic, in order to maintain interest in a new, hybrid, certificate floral design program titled “Master Floral Designer,” initiated in 2017. Encouraged by high ratings, Extension presented the course in person in 2021. With continued high participant ratings and lower COVID transmission rates, Extension faculty and staff planned to offer the program in 2022 at six locations statewide to increase awareness and enrollment in the certificate program. Results from the statewide workshop showed that 86% (n=32) of the students agreed to strongly agreed to participate in Extension floral design courses toward a certificate, with 14% (n=5) neutral. Three participants enrolled in the certificate program the following year. The students wanted to purchase locally grown, cut evergreens (95%) and were willing to buy designs like their own using locally grown evergreens 84% (n=37).